Determination of the Installation Efficiency of Vertical Stationary Photovoltaic Modules with a Double-Sided “East–West”-Oriented Solar Panel - Golub, Gennadii; Blažauskas, Egidijus; Tsyvenkova, Nataliya; Šarauskis, Egidijus; Jasinskas, Algirdas; Kukharets, Savelii; Nadykto, Volodymyr; Надикто, Володимир Трохимович; Holubenko, Anna (My University, 2025)
The objects of this research are double-sided stationary vertical photovoltaic modules (PV-modules) with an “East–West”-oriented solar panel. The tilt angles of the Sun’s rays on PV-modules at a latitude of 50◦ were determined, and the installation effi ciencies of both double-sided stationary vertical PV-modules with an “East–West” oriented panel and PV-modules installed at an angle of latitude with a “South” oriented panel were by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/ licenses/by/4.0/). compared. The horizontal azimuth of the fall of the Sun’s rays during the day when using PV-modules with an “East–West”-oriented panel reaches a minimum at noon. The vertical azimuth of the Sun’s rays remains constant throughout the day and can vary from 66.55◦ to 113.45◦. The weighted average daily installation efficiency of PV-modules with an “East West”-oriented panel has the same value as that of PV-modules with a “South”-oriented panel, and can vary between 45.87 and 50% on different days. However, these installation options have a “mirror” value of the cosines of the Sun’s rays falling on the surface of the PV-modules and can have values from 0.917 to 1. The results can be used as a basis for evaluating the efficiency of double-sided vertical stationary solar PV-modules with an “East–West”-oriented panel.
Keywords: PV-module; “East–West”-oriented solar panel; module installation efficiency; double-sided vertical PV-module; “South”-oriented solar panel